FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA BIDAN PADA PELAYANAN ANTENATAL CARE DI PUSKESMAS SEKOTA PALEMBANG TAHUN 2014 - Wargustini Wargustini (STIKes Budi Mulia Sriwijaya, 2014)
ABSTRACK This study aimed to determine the knowledge, motivation, leadership, incentives / rewards, and education with the performance of midwives in Antenatal Care Services (ANC) at health centers in the country Palembang, this study uses observational analytic study design